2017
DOI: 10.1016/j.exger.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-assessed light physical activity is protective of future cognitive ability: A longitudinal study among community dwelling older adults

Abstract: Objective (246/250)Physical activity (PA), especially moderate-to-vigorous intensity, could protect older adults from cognitive impairment. However, most literature is based on self-reported PA which is limited by recall bias. Light PA is popular among older adults, but a paucity of objective longitudinal data has considered the relationship between light PA and cognitive ability. We examined if a higher level of objectively measured light PA, independent of moderate-to-vigorous physical activity (MVPA), was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 34 publications
9
81
1
1
Order By: Relevance
“…The results of adjusted analysis indicated that there were no significant patterns in relations between physical activity and cognitive decline in any of the three states. These findings differed from previous research that showed physical activity to be a neuroprotective factor [1][2][3][4][7][8][9].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The results of adjusted analysis indicated that there were no significant patterns in relations between physical activity and cognitive decline in any of the three states. These findings differed from previous research that showed physical activity to be a neuroprotective factor [1][2][3][4][7][8][9].…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, this study examined females ages 55 to 64, whereas most previous research focused on the elderly [1,[6][7][8]12]. The variables in this study were concurrent levels of cognitive decline and physical activity levels at one point in time; therefore, benefits of physical activity for cognitive decline may not be immediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A waist-worn triaxial accelerometer was used by 274 community-dwelling older adults over 22 months. Light physical activity (measured by the accelerometer and defined using established cut-offs28) was independently associated with lower scores (ie, better cognitive function) on the AD8—an eight-item informant interview probing memory, orientation, judgement and ADLs29 at follow-up 27. The study suggested that promotion of higher levels of objectively measured light physical activity could help protect cognitive function in older adults.…”
Section: Presentationmentioning
confidence: 87%
“…One study used accelerometer data to monitor older adults’ physical activity, intending to infer cognitive status 27. A waist-worn triaxial accelerometer was used by 274 community-dwelling older adults over 22 months.…”
Section: Presentationmentioning
confidence: 99%